PRINSIP KETIDAKPASTIAN HEISENBERG DALAM TINJAUAN KEMAJUAN PENGUKURAN KUANTUM DI ABAD 21 - Jesi Pebralia (Prodi Fisika FST UNJA, 2020)
The Heisenberg uncertainty principle is the basic foundation of quantum physics that characterizes quantum physics with classical physics. The Heisenberg uncertainty principle provides boundaries where there are no absolute measurement results in any quantum measurement. Along with the development of increasingly sophisticated measurement instruments in the 21st century, presents the opportunity for the emergence of modifications from the Heisenberg uncertainty principle from the general form of existing formulations. This study aims to provide an overview of the opportunities for Heisenberg uncertainty formulation and provide a description of the stages of the Heisenberg uncertainty formulation's uncertainty formulations that have been reviewed by previous researchers. The research method used is the method of literature study that aims to find out the background and theories of the development of Heisenberg's uncertainty principle and to explain the formulation directly which aims to determine the technical sequence of modifications to the existing formulation. Through this research, the authors managed to get an opportunity for the emergence of new modifications to the Heisenberg uncertainty principle formulation.